Optical Photometric Monitoring of the Blazar OT 355 and Local Standard Stars’ Calibration - R. Bachev; Tushar Tripathi; Alok C. Gupta; A. Kurtenkov; Y. Nikolov; A. Strigachev; S. Boeva; G. Latev; B. Spassov; M. Minev; E. Ovcharov; W.-X. Yang; et al. (Universe)
OT 355 (4FGL J1734.3 + 3858) is a relatively rarely studied but highly variable, moderate-redshift (z = 0.975) flat-spectrum radio quasar (blazar). With this work, we aim to study its optical variability on different timescales, which can help us to better understand the physical processes in relativistic jets operating in blazar-type active galactic nuclei. OT 355 was observed in four colors (BVRI) during 41 nights between 2017 and 2023 using three 1 and 2 m class telescopes. The object was also monitored on intra-night timescales, for about 100 h in total. In addition, secondary standard stars in the field of OT 355 were calibrated in order to facilitate future photometric studies. We detected significant intra-night and night-to-night variations of up to 0.5 mag. Variability characteristics, color changes, and a possible “rms-flux” relation were studied and discussed. Using simple arguments, we show that a negative “rms-flux” relation should be expected if many independent processes/regions drive the short-term variability via Doppler factor changes, which is not observed in this and other cases. This finding raises arguments for the idea that more complex multiplicative processes are responsible for blazar variability. Studying blazar variability, especially on the shortest possible timescales, can help to estimate the strength and geometry of their magnetic fields, the linear sizes of the emitting regions, and other aspects, which may be of importance for constraining and modeling blazars’ emitting mechanisms.